Impaired Immune Phenotype of Circulating Endothelial-Derived Microparticles in None-Diabetic Patients with Chronic Heart Failure: Impact on Insulin Resistance - Berezin, Alexander E; Kremzer, Alexander A; Samura, Tatyana A; Berezina, Tatyana A (Journal of Cells, 2015)
Background: The causality role of different immune phenotype in IR developing among chronic heart failure (CHF) subjects has not determined obviously. The aim of the study was to assess relationship between IR and immune phenotype of circulating endothelial-derived microparticles (EMPs) in patients with CHF. Methods: The study retrospectively involved 300 CHF patients aged 48 to 62 years. All the patients have given written informed consent for participation in the study. Biomarkers were measured at baseline of the study. Results: These were not significant differences between both cohort patients in EMPs labeled as CD144+/CD31+, CD144+/annexin V+, and CD62E+ microparticles. Higher concentrations of CD144+/CD31+/annexin V+ EMPs and CD31+/annexin V+ EMPs were found in IR subjects when compared with none IR patients. Using multivariate logistic regression analyses, we found that HOMA-IR (OR = 1.14, 95% CI=1.08-1.21, P = 0.001), NT-proBNP (OR = 1.07, 95% CI=1.04-1.10, P = 0.001), hs-CRP (OR = 1.04, 95% CI=1.02-1.07, P = 0.001), and NYHA class (OR = 1.03, 95% CI=1.01-1.05, P = 0.001) were predictors for increased CD31+/annexin V+ EMPs. Therefore, HOMA-IR (OR = 1.10, 95% CI=1.05-1.17, P = 0.001), NT-proBNP (OR = 1.08, 95% CI=1.04-1.12, P = 0.001), and NYHA class (OR = 1.05, 95% CI=1.02-1.09, P = 0.001) significantly predicted elevation of CD144+/CD31+/annexin V+ EMPs. Conclusion: we found that IR remains statistically significant predictor for increased apoptotic-derived EMPs labelled as CD144+/CD31+/annexin V+ and CD31+/annexin V+ EMPsin none-diabetic patients with CHF patients and that these findings reflect exiting impaired phenotype of circulating EMPs in this patient population.